Genetic counselor experiences with telehealth before and after COVID‐19. Issue 4 (7th July 2021) - Mills, Rachel; MacFarlane, Ian M; Caleshu, Colleen; Ringler, Margaret A; Zierhut, Heather A
Abstract: While genetic counselor (GC) utilization of telehealth has increased in recent years, the onset of the COVID‐19 pandemic significantly accelerated the adoption of telehealth for many. We investigated GC experiences with telehealth including perceived advantages, disadvantages, and barriers using a one‐time online survey of GCs who provided direct patient care in recent years. The survey examined experiences with telehealth before and after the onset of COVID‐19. We made broad comparisons to findings from a similar study our research team conducted five years ago. GCs reported an increase in the utilization of telehealth over time, with significant increases from pre‐2017 (44%) to pre‐COVID‐19 (70%) and then to present (87%) ( p <.001 and .02, respectively). There was no significant change in the total number of hours worked from pre‐COVID‐19 to the time of survey completion, nor were there significant changes in the amount of time spent on clinical responsibilities or interfacing with patients. However, the total number of hours worked in telehealth significantly increased (z = 5.05, p <.001) as did the percent of time spent interacting with patients via telehealth [t(72)=3.74, p <.001, d = 0.44]. Participants overwhelmingly preferred video (84%) over telephone; this differs from our previous survey where video was the preferred modality for 59% ( p <.001). We utilized open‐ended questions to elicit reasons for modality preference. The most‐cited barrier to telehealth utilization was billing/reimbursement issues, with 39% noting this obstacle. This is consistent with our previous study where 30% cited billing/reimbursement as the primary barrier. These findings indicate a need for continued efforts to improve billing and reimbursement for genetic counseling offered via telehealth. They also present an opportunity for additional exploration regarding patient preferences for telehealth modality.